Measurement and Reversal of Prophylactic and Therapeutic Peak Levels of Rivaroxaban: An In Vitro Study. (October 2014) - Körber, Mareike Kristina; Langer, Elisabeth; Ziemer, Sabine; Perzborn, Elisabeth; Gericke, Christine; Heymann, Christian von
Background: Rivaroxaban (Xarelto, Bayer HealthCare, Leverkusen, Germany) is a new oral anticoagulant drug. Anticoagulants may cause bleeding, thereby requiring reliable monitoring and efficient therapy. We investigated thromboelastometry versus routine coagulation tests to measure prophylactic and therapeutic concentrations of rivaroxaban and their reversal with prothrombin complex concentrate (PCC) and activated recombinant factor VII (rFVIIa) in vitro. Methods: Rivaroxaban was solubilized, and PCC and rFVIIa were added in 2 concentrations to the rivaroxaban-spiked blood samples, and thromboelastometry and measurements were performed. Results: Rivaroxaban increased tissue factor–activated clotting time (CTExTEM ) dose dependently. Activated partial prothrombin time (aPTT), prothrombin time ratio (PTR), and prothrombin time (PT) were changed significantly in both concentrations. Reversal with PCC in both dosages caused no significant change in the measured parameters. For prophylactic rivaroxaban dosage, rFVIIa changed the PT significantly but not CTExTEM, aPTT, and PTR. For therapeutic rivaroxaban dosage, the CTExTEM was significantly reduced. The other parameters remained unaffected. Conclusions: Thromboelastometry can detect rivaroxaban effects. In vitro rFVIIa seems highly effective for reversal in contrast to PCC.